Baseline Inhibin B and Anti-Mullerian Hormone Measurements for Diagnosis of Hypogonadotropic Hypogonadism (HH) in Boys with Delayed Puberty - Coutant, Régis; Biette-Demeneix, Estelle; Bouvattier, Claire; Bouhours-Nouet, Natacha; Gatelais, Frédérique; Dufresne, Sylvie; Rouleau, Stéphanie; Lahlou, Najiba (The journal of clinical endocrinology and metabolism, 2010)
Context: The diagnosis of isolated hypogonadotropic hypogonadism (IHH) in boys with delayed puberty is challenging, as may be the diagnosis of hypogonadotropic hypogonadism (HH) in boys with combined pituitary hormone deficiency (CPHD). Yet, the therapeutic choices for puberty induction depend on accurate diagnosis and may influence future fertility. Objective: The aim was to assess the utility of baseline inhibin B (INHB) and anti-Mullerian hormone (AMH) measurements to discriminate HH from constitutional delay of puberty (CDP). Both hormones are produced by Sertoli cells upon FSH stimulation. Moreover, prepubertal AMH levels are high as a reflection of Sertoli cell integrity. Patients: We studied 82 boys aged 14 to 18 yr with pubertal delay: 16 had IHH, 15 congenital HH within CPHD, and 51 CDP, as confirmed by follow-up. Subjects were genital stage 1 (testis volume <3 ml; 9 IHH, 7 CPHD, and 23 CDP) or early stage 2 (testis volume, 3–6 ml; 7 IHH, 8 CPHD, and 28 CDP). Results: Age and testis volume were similar in the three groups. Compared with CDP subjects, IHH and CPHD subjects had lower INHB, testosterone, FSH, and LH concentrations (P < 0.05), whereas AMH concentration was lower only in IHH and CPHD subjects with genital stage 1, likely reflecting a smaller pool of Sertoli cells in profound HH. In IHH and CPHD boys with genital stage 1, sensitivity and specificity were 100% for INHB concentration of 35 pg/ml or less. In IHH and CPHD boys with genital stage 2, sensitivities were 86 and 80%, whereas specificities were 92% and 88%, respectively, for an INHB concentration of 65 pg/ml or less. The performance of testosterone, AMH, FSH, and LH measurements was lower. No combination or ratio of hormones performed better than INHB alone. Conclusion: Discrimination of HH from CDP with baseline INHB measurement was excellent in subjects with genital stage 1 and fair in subjects with genital stage 2.